A Brief Case Series On The Clinical Psychologist's Role In Inpatient Pain Management (Journal of Pharmaceutical Negative Results, 2014)
According to recent studies, between 25% and 33% of all hospitalized patients endure intolerable pain. Additionally, studies show that this raises costs, lengthens hospital stays, and lowers patient satisfaction levels. Adequate pain management may be hampered by hospitals' efforts to discharge patients earlier. As a result, Chelsea and Westminster Hospital's pain service has adjusted to this evolving care paradigm. A growing amount of research indicates that psychological aspects play a significant role in how patients experience both acute and chronic pain.Therefore, it makes sense to recommend that inpatient pain management involve a clinical psychologist. This brief study examines three instances that demonstrate how adding a clinical psychologist to the inpatient pain team could enhance patient care. The active role of the psychologist in diagnosing and treating common conditions like anxiety and fear, as well as other psychiatric comorbidities, is especially demonstrated by two cases. Behavioral, cognitive behavioral, and dialectical behavioral therapeutic techniques were combined with brief counseling to create an eclectic approach that was adapted from chronic pain.The significance of nurse-patient interactions and the impact of the quality of nurse-patient relationships on patient outcomes are best illustrated by the third case. In this case, the psychologist assisted in improving communication and resolving a challenging and possibly dangerous circumstance. The advantages of having a clinical psychologist involved in inpatient pain management are covered in this brief case series, which highlights the need for innovative inpatient pain services initiatives. Future studies are necessary to validate this strategy, though.